Outpatient CBT for Underweight Patients with Eating Disorders: Effectiveness Within a National Health Service (NHS) Eating Disorders Service. Issue 2 (2nd August 2018) - Jenkins, Paul E.; Morgan, Ceri; Houlihan, Catherine
Abstract : Background: Underweight eating disorders (EDs) are notoriously difficult to treat, although a growing evidence base suggests that outpatient cognitive behaviour therapy for EDs (CBT-ED) can be effective for a large proportion of individuals.Aims: To investigate the effectiveness of CBT-ED for underweight EDs in a 'real-world' settings.Method: Sixty-three adults with underweight EDs (anorexia nervosa or atypical anorexia nervosa) began outpatient CBT-ED in a National Health Service setting.Results: Fifty-four per cent completed treatment, for whom significant changes were observed on measures of ED symptoms, psychological distress and psychosocial impairment. There was also a large effect on body weight at end-of-treatment.Conclusions: The results suggest that good outcomes can be achieved by the majority of those who complete treatment, although treatment non-completion remains a significant barrier to recovery. Future studies should focus on improving treatment retention, as evidence suggests that CBT-ED in 'real-world' settings is effective.